PSORIASIS IS ASSOCIATED WITH ELEVATED GUT IL-1Α AND INTESTINAL MICROBIOME ALTERATIONS - Yegorov, Sergey; Babenko, Dmitriy; Kozhakhmetov, Samat; Akhmaltdinova, Lyudmila; Kadyrova, Irina; Nurgozhina, Ayaulym; Nurgaziyev, Madiyar; Good, Sara V.; Hortelano, Gonzalo H.; Yermekbayeva, Bakytgul; Kushugulova, Almagul (Frontiers in Immunology, 2020)
Psoriasis is a chronic inflammatory condition that predominantly affects the skin and is associated with extracutaneous disorders, such as inflammatory bowel disease and arthritis. Changes in gut immunology and microbiota are important drivers of proinflammatory disorders and could play a role in the pathogenesis of psoriasis. Therefore, we explored whether psoriasis in a Central Asian cohort is associated with alterations in select immunological markers and/or microbiota of the gut.
Keywords: Type of access: Open Access; Psoriasis; immunology